Anopheles bionomics, insecticide resistance and malaria transmission in southwest Burkina Faso: A pre-intervention study. - Dieudonné Diloma Soma; Barnabas Mahugnon Zogo; Anthony Somé; Bertin N'Cho Tchiekoi; Domonbabele François de Sales Hien; Hermann Sié Pooda; Sanata Coulibaly; Jacques Edounou Gnambani; Ali Ouari; Karine Mouline; Amal Dahounto; Georges Anicet Ouédraogo; et al. (PLoS ONE, 2020)
Background Twenty-seven villages were selected in southwest Burkina Faso to implement new vector control strategies in addition to long lasting insecticidal nets (LLINs) through a Randomized Controlled Trial (RCT). We conducted entomological surveys in the villages during the dry cold season (January 2017), dry hot season (March 2017) and rainy season (June 2017) to describe malaria vectors bionomics, insecticide resistance and transmission prior to this trial. Methods We carried out hourly catches (from 17:00 to 09:00) inside and outside 4 houses in each village using the Human Landing Catch technique. Mosquitoes were identified using morphological taxonomic keys. Specimens belonging to the Anopheles gambiae complex and Anopheles funestus group were identified using molecular techniques as well as detection of Plasmodium falciparum infection and insecticide resistance target-site mutations. Results Eight Anopheles species were detected in the area. Anopheles funestus s.s was the main vector during the dry cold season. It was replaced by Anopheles coluzzii during the dry hot season whereas An. coluzzii and An. gambiae s.s. were the dominant species during the rainy season. Species composition of the Anopheles population varied significantly among seasons. All insecticide resistance mechanisms (kdr-w, kdr-e and ace-1 target site mutations) investigated were found in each members of the An. gambiae complex but at different frequencies. We observed early and late biting phenotypes in the main malaria vector species. Entomological inoculation rates were 2.61, 2.67 and 11.25 infected bites per human per month during dry cold season, dry hot season and rainy season, respectively. Conclusion The entomological indicators of malaria transmission were high despite the universal coverage with LLINs. We detected early and late biting phenotypes in the main malaria vector species as well as physiological insecticide resistance mechanisms. These data will be used to evaluate the impact of complementary tools to LLINs in an upcoming RCT.